Reendothelization of porcine heart valve scaffolds with WJ-MSC: a new approach in the heart valve tissue engineering. - Lanuti, Paola; Serafini, Francesco; Pierdomenico, Laura; Bologna, Giuseppina; Ercolino, Eva; Grifone, Giovanna; Pantalone, Mattia Russel; Di Giammarco, Gabriele; Marchisio, Marco; Miscia, Sebastiano (Italian Journal of Anatomy and Embryology, 2015)
Heart valve substitution, based on biosynthetic or mechanical prosthesis replacement, is one of the most frequent surgical approach to treat heart valve diseases. Even if the prosthesis implantation gives a good life quality for patients, there are many long-term disadvantages related to the substitution, such as structural deterioration, non-structural dysfunction and re-intervention. The heart valve tissue engineering (HVTE), a novel branch of regenerative medicine, is developing innovative models and testing new methods to overcome the above reported limitations. In the present study, we investigated the possibility to reendothelize a porcine heart valve scaffold, previously decellularized, by using two cell types: Wharton’s Jelly mesenchymal stem cells (WJ-MSC) and human umbilical vein endothelial cells (HUVEC), the last used as control cells for the reendothelialization process. Both cell types showed, by fluorescence microscopy, that they were able to reconstitute a valid and functional monolayer of neo-endothelium, characterized by the surface expression of typical endothelial markers (i.e. CD144 and CD146). All together, these data suggest that both HUVEC and WJ-MSC are suitable for in vitro autologous endothelium regeneration, opening new perspectives in the field of HVTE.